Effect of Moringa oleifera leaf powder on drying kinetics, physico‐chemical properties, ferric reducing antioxidant power, α‐tocopherol, β‐carotene, and lipid oxidation of dry pork sausages during processing and storage. Issue 1 (24th November 2019) - Mukumbo, Felicitas E.; Descalzo, Adriana M.; Collignan, Antoine; Hoffman, Louwrens C.; Servent, Adrien; Muchenje, Voster; Arnaud, Elodie
Abstract: The potential of Moringa oleifera leaf powder (MLP) to limit lipid oxidation in nitrite‐free unfermented dry pork sausages (droëwors) was investigated. Total phenolic compounds, α‐tocopherol and β‐carotene content of MLP was quantified. Droëwors with no additives, 0.75 g/100 g MLP or 15 mg/kg vitamin E (VE) oil were processed and sampled after drying (3 days) and during 56 days of storage. Thiobarbituric acid reactive substances (TBARS) of droëwors made with MLP were lower until day 10. The effects of 0, 0.5, 1, and 2 g/100 g MLP on TBARS, ferric reducing antioxidant power (FRAP) and the α‐tocopherol, γ ‐ tocopherol, and β‐carotene content of droëwors were assessed during drying and 7 days of storage. MLP inclusion significantly increased FRAP, α‐tocopherol, and β‐carotene content. From the end of drying, TBARS of droëwors formulated with MLP were significantly lower compared to droëwors formulated without MLP. Increasing the MLP inclusion level had no significant effect on TBARS. Practical applications: The research assesses and demonstrates the potential of Moringa oleifera leaf powder (MLP) as a natural additive to inhibit the rate and extent of lipid oxidation in unfermented dry pork sausages (droëwors) with no nitrites/nitrates added. The inclusion of MLP in pork droëwors at levels ranging from 0.5 to 2 g/100 g significantly increased the antioxidant activity (FRAP) and quantity of antioxidant vitamins (α‐tocopherol, and β‐carotene) in the product. Higher inhibition of lipid oxidation (TBARS) was observed in droëwors with MLP added compared to the positive (vitamin E oil) and negative (no additives) controls. The different MLP inclusion levels used in the study resulted in similar lipid oxidation inhibition. Therefore, the findings show that the application of 0.5 g/100 g MLP is sufficient to decrease lipid oxidation in pork droëwors and could potentially be applied to other types of dry‐cured sausages for this purpose.